2002
DOI: 10.1034/j.1600-0625.2002.110403.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parathyroid hormone‐related protein on fibroblast proliferation and collagen metabolism in human skin

Abstract: The parathyroid hormone-related protein (PTHrp), structurally similar to the parathyroid hormone (PTH) in its NH(2)-terminal part, was first identified as a tumour-derived peptide responsible for a paraneoplastic syndrome known as humoral hypercalcemia of malignancy. The PTHrp gene is expressed not only in cancer but also in normal tissues during adult and/or fetal life, where it plays predominantly paracrine and/or autocrine roles. In the skin PTHrp produced by keratinocytes acts on fibroblasts by complex coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…PTHrP: The PTHrP inhibits proliferation of dermal fibroblasts in a dose dependent manner, whereas a dose-dependent stimulation of cAMP, released by fibroblasts, can be concomitantly observed 57 . In contrast, PTHrP has no effect on collagen synthesis, whereas it increases metalloproteinase 2 activity.…”
Section: Biological Activity Of Hormones In Human Skinmentioning
confidence: 99%
“…PTHrP: The PTHrP inhibits proliferation of dermal fibroblasts in a dose dependent manner, whereas a dose-dependent stimulation of cAMP, released by fibroblasts, can be concomitantly observed 57 . In contrast, PTHrP has no effect on collagen synthesis, whereas it increases metalloproteinase 2 activity.…”
Section: Biological Activity Of Hormones In Human Skinmentioning
confidence: 99%
“…ADRP is necessary for the trafficking of substrate for surfactant production (43), and leptin stimulates the differentiation of the alveolar type II cell (50). PTHrP affects the cellular composition of the alveolar interstitium in at least three ways: 1) it inhibits fibroblast growth (28) and stimulates apoptosis (36), causing septal thinning, 2) stimulation of epithelial type II cell differentiation by leptin (50) can inhibit epithelial cell growth (36), and 3) leptin may upregulate type IV collagen synthesis (60), reinforcing the alveolar wall (24).…”
Section: Ontogeny and Homeostasismentioning
confidence: 99%
“…Evidence for such a role is also confirmed by studies with PTHrP knockout mice that, in addition to chondrodystrophy, displayed several cutaneous abnormalities, including a fibrotic dermis [15]. These data are linked to pathophysiological events such as wound healing, skin aging and tumor progression in which either PTHrP, cell proliferation or MMP activity are implicated [14].…”
Section: Discussionmentioning
confidence: 77%
“…Recent studies in our laboratory have demonstrated the role of PTHrP in modulating cell proliferation and extracellular matrix turnover (MMP2) in primary skin fibroblasts obtained from a single human donor [14]. Evidence for such a role is also confirmed by studies with PTHrP knockout mice that, in addition to chondrodystrophy, displayed several cutaneous abnormalities, including a fibrotic dermis [15].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation